Letter from G. F. Hulek to Dr. Paul D. V. Manning - Hulek, G. F. (1955)
Hulek, Arnold Beckman's secretary, responds to a letter from Manning requesting the overhaul of a spectrophotometer. She explains that Beckman himself is in Nevada observing an atomic bomb test.
Keywords: Atomic bomb--Testing; Ultraviolet spectroscopy; Scientific apparatus and instruments; Spectrophotometer; Beckman Instruments, Inc.